2003
DOI: 10.1108/03321640310452196
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of the temperature field and melt flow in the induction furnace with cold crucible

Abstract: Comprehensive knowledge of the complicated physical behavior of the induction furnace with cold crucible (IFCC) is required to utilize the advantages of this melting aggregate in melting and casting chemically high-reactive materials, like titanium-aluminides (TiAl). Practical experiences show that the overheating temperature of the melt is decisive for the quality of the cast products. Therefore, a systematic analysis of the electromagnetic and in particular, the hydrodynamic and thermal behavior of the IFCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…[6,7] The stirring processes and the melt flow in an ICF have been studied both numerically and experimentally for a long time. [8][9][10][11][12][13][14] Baake et al [8] demonstrated that the predictions, obtained with the standard k-e turbulence model are able to provide a good agreement with the experimentally determined time-averaged velocity field. However, the low-frequency pulsations in the velocity, which occur in the region between the main long-term vortices, prove difficult to be captured by adopting this model.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…[6,7] The stirring processes and the melt flow in an ICF have been studied both numerically and experimentally for a long time. [8][9][10][11][12][13][14] Baake et al [8] demonstrated that the predictions, obtained with the standard k-e turbulence model are able to provide a good agreement with the experimentally determined time-averaged velocity field. However, the low-frequency pulsations in the velocity, which occur in the region between the main long-term vortices, prove difficult to be captured by adopting this model.…”
Section: Introductionmentioning
confidence: 88%
“…The Large eddy simulation (LES) was found to be a good variant for more accurate predication of the low-frequency fluctuations and the temperature distribution in the melt. [9][10][11][12] Schwarze et al [14] performed an unsteady Reynolds averaged Navier-Stokes simulation (URANS) in order to investigate the turbulent melt flow in an ICF adopting the Reynolds stress turbulence model. Using this turbulence model, the predicted results showed the presence of the large flow structure with low frequency fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Many numerical and experimental investigations have been carried out to predict melt flow in an ICF. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Numerous authors have reported that the large eddy simulation (LES) produces fairly accurate heat and mass transfer predictions, compared with the unsteady Reynolds-averaged Navier-Stokes (URANS) simulations. [9][10][11][12][13] In addition to simulating and studying the melt flow, other authors have investigated inclusions transport in an ICF.…”
Section: Introductionmentioning
confidence: 99%
“…Practical experiences show that the overheating temperature of the entire melt, which is determined by the electromagnetic, hydrodynamic and thermal process factors, is one of the key parameters of this technological process. Due to its importance for modern industry it has become the subject for numerical modeling [1][2][3]. The task of optimising melt overheating faces the challenge of finding optimal combination of crucible height to diameter ratio, number of inductor turns and crucible sections, current strength and frequency.…”
Section: Introductionmentioning
confidence: 99%